Opana-induced thrombotic microangiopathy masquerading as thrombotic thrombocytopenic purpura - Ban, Byung H. (Oxf Med Case Reports, 2017)
Opana (oxymorphone) is a powerful semi-synthetic opioid agonist used for chronic pain management that is ingested orally. However, improper injection of Opana can lead to a rare and fatal blood disorder known as thrombotic microangiopathy. Opana-induced thrombotic microangiopathy can be easily mistaken for thrombotic thrombocytopenic purpura (TTP), leading to the initiation of therapeutic plasma exchange. Current literature has conflicting views on the necessity of therapeutic plasma exchange for the treatment of Opana-induced thrombotic microangiopathy. In our case report, a 47-year-old Caucasian male was admitted with a presentation suspicious for TTP then underwent therapeutic plasma exchange without clinical improvement. With supportive treatment only, the patient eventually improved and later admitted to intravenously abusing oral Opana 1–2 days prior to becoming ill.